Time Relationships Among Electricity and Fossil Fuel Prices: Industry and Households in Europe - Madaleno, Mara; Moutinho, Victor; Mota, Jorge (International Journal of Energy Economics and Policy, 2015)
Cointegration relationships among electricity, gas, oil and coal are explored using panel data models for both the industrial and household sectors in 22 countries in Europe between 1996 and 2013. A shorter period, to account for the allowances market creation in Europe is also considered through a dummy (2005-2013) to capture the absence and presence of the CO2 price effect respectively. Empirical findings reveal that electricity and fuel prices are non-stationary and cointegrated series. So, the current paper accounts for cross-section dependence when analyzing the electricity-fuel nexus. Results indicate that there exists a stronger long run equilibrium relationship between electricity prices and fuel prices in the industry sector, while both a short and long run equilibrium relationship in the household sector. These differences may be explained by the industry higher resilience in long run contracts within the energy sector and by the fact that households bear a larger share of the cost of taxes and levies. Keywords: Cointegration; Electricity and fuel markets; Industrial and Household sectors JEL Classifications: O52; Q02; Q50